Expected Coordination and Unexpected Transformation of the Bis (Diphenylphosphino)methane in the Platinum(II) Complex - Faihan, Ahmed S.; Aziz, Nazk Mohammed; Ashfaq, Muhammad; Behjatmanesh-Ardakani, Reza; Al-Janabi, Ahmed S.; Tahir, Muhammad Nawaz; Yousef, Tarek A. (Elsevier, 2025)
The reaction of a Platinum(II)-DMSO complex with bis(diphenylphosphino)methane (dppm) yielded two distinct complexes. The major product was identified as [PtCl2(dppm)], demonstrating the expected coordination of the intact dppm ligand. However, the minor product exhibited an unexpected transformation, characterized by the cleavage of the dppm carbon bridge, resulting in a phosphorus atom bonded to two phenyl groups and a hydrogen atom. Both complexes were thoroughly investigated using single-crystal X-ray diffraction (SCXRD) and computational methods to determine their quantum parameters. SCXRD analysis revealed that both structures are mononuclear Pt complexes in which the phosphorus atoms of the ligands and the chloride ligands coordinate to the platinum center, adopting a highly distorted tetrahedral geometry. The minor product's structure displayed disorder, with a portion containing an HCl molecule, which was absent in the major product's structure. An analysis of intermolecular interactions revealed various hydrogen-bonding interactions, with chloride atoms acting as hydrogen-bond acceptors. Molecular interactions were further examined using Hirshfeld surface analysis. Density Functional Theory (DFT) calculations were performed using the Def2-SVPD basis set and the B3LYP hybrid functional to investigate the complexes' electronic properties. The computational results showed good agreement with the experimental findings. Furthermore, the energies and distributions of the highest occupied molecular orbital (HOMO) and lowest unoccupied molecular orbital (LUMO) were determined. Finally, molecular docking studies were conducted with Ampicillin-CTX-M-15, which demonstrated a favorable binding interaction between the ligand and targeted amino acid residues, with a binding score of -5.26 kcal/mol.
Al-Janabi, Ahmed/0000-0003-2722-7419; Al-Janabi, Ahmed/0000-0003-2722-7419;
Keywords: Bis(Diphenylphosphino)Methane; Platinum(II) Complexes; Ligand Cleavage; DFT